Successful Percutaneous Closure of a Residual Atrial Septal Defect Due to Device Failure - Aguiar Rosa, S (2017)
A 39-year-old woman underwent uneventful percutaneous occlusion of an ostium secundum atrial septal defect (ASD) with a 22 mm Ultrasept ASD Occluder®. Transesophageal echocardiography (TEE) performed two years after implantation revealed a de novo residual left-to-right shunt through the correctly implanted device. Three-dimensional transesophageal echocardiography (3D TEE) further clarified this finding by showing a perforation of the device membrane coating. The patient underwent transcatheter closure of the residual shunt with a 20 mm Ultrasept PFO®device. The procedure was guided by fluoroscopy and real-time 3D TEE. At the end of the procedure 3D TEE documented correct device deployment with complete defect coverage and absence of residual shunt.